Notes from the Executive Editor - Yohanes Sulaiman (Journal Of Global Strategic Studies, 2022)
As the executive editor, I would like to thank our readers, authors, reviewers, and our editorial staff for your continuous interest and support to Journal of Global Strategic Studies. With all of your support and prayers, we are able to achieve a new milestone of continuous publications of excellent scholarly works for the past two years. I am hoping that as we are approaching the end of 2022, the new year will bring more positive changes and developments to our journal.